1993
DOI: 10.1111/j.1432-1033.1993.tb19874.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping and immunoinactivation of human gastric lipase using five monoclonal antibodies

Abstract: Five monoclonal antibodies (mAb) directed against human gastric lipase (HGL) have been produced by hybridization of myeloma cells with spleen cells of BALB/c immunized mice. All these mAb belong to the IgGl class with a K light chain. The effects of these mAb on the enzymic activity of HGL were studied and used to define three classes of antibodies, depending upon their immunoinactivation properties. As determined by ELISA and immunoinactivation studies, four overlapping epitopes were found to be part of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The fact that D242N/D254N/E210Q reacts extremely heteroclitically indicates that the charge removing effect is additional and that this variant is more antigenic than the remaining one. This is in agreement with what has been found for gastric lipase, where four out of five MoAb recognized the same hydrophobic surface epitope [5]. However, the result contradicts that found for hydrophihc proteins.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The fact that D242N/D254N/E210Q reacts extremely heteroclitically indicates that the charge removing effect is additional and that this variant is more antigenic than the remaining one. This is in agreement with what has been found for gastric lipase, where four out of five MoAb recognized the same hydrophobic surface epitope [5]. However, the result contradicts that found for hydrophihc proteins.…”
Section: Discussionsupporting
confidence: 91%
“…Epitope mapping in a number of proteins revealed that these six amino acids are the most frequent in the analysed epitopes [4], and that antigenicity appears to be determined both by the local mobility of the region containing the epitope, and the frequency of antigenic residues. A hydrophobic epitope was identified in gastric lipase, on the surface of the folded protein to which four of the five tested monoclonal antibodies (MoAb) bound [5], thus neither the antigenicity ofthe epitope nor its individual residues reflected the properties described for the hydrophilic proteins mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Two ELISA methods were developed for this study. First, a simple sandwich ELISA was carried out by coating the plates with 500 ng of pure HPUwell using an identical proc edure to that previously described by Aoubala et al (13). Second, a double sandwich ELISA was performed by coating the plates with 500 ng of pure anti-HPL pAb/well (captor antibody).…”
Section: Methodsmentioning
confidence: 99%
“…Bri efly, microtiter plates were coated with 2.5 ng of native HPU well, and mAbs were cotitrated in pairs at a molar ratio of 1:1. The ELISA procedure was performed as described previously by Aoubala et al (13 ).…”
Section: ~Imentioning
confidence: 99%
See 1 more Smart Citation